The Civil War Rifleman - Windrow, Martin; Burn, Jeffrey (Franklin Watts New York, 1985)
Examines the life and experiences of a typical Union and Confederate soldier during the Civil War. Includes a glossary of terms and a brief chronology of major events in the war.
Includes bibliographical references and index.
Keywords: Armed Forces Military life; Army History -- United States. -- Civil War -- 1861-1865 -- Juvenile literature; Confederate States of America. -- Army Military life